Impact of the road improvement project on household consumption: evidence from Nepal - Koirala, Sabin (Journal of Engineering Issues and Solutions, 2023)
This study examines the impact of road improvement project on the household consumption of food and non-food items from different sources such as self-produced and the market purchases. Using the household-level data pooled from the Annual Household Survey (2013-2016) and road network database, this study relies on the “difference-in-difference” method. The results suggest that the road improvement project was associated with a significant increase in the market-purchased household consumption. Market purchased food consumption and non-food consumption increased significantly by 21% and 31% following the implementation of the project. The impact is much more profound in rural households with the shift in their source of consumption from production to market purchase. These findings are consistent to robustness check using an unmatched sample and pre-trend analysis. We conclude that the improvement of road network improves consumption and thus the household welfare.